1996
DOI: 10.1073/pnas.93.8.3598
|View full text |Cite
|
Sign up to set email alerts
|

Protein-free cell culture on an artificial substrate with covalently immobilized insulin.

Abstract: Insulin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 27 publications
3
80
0
Order By: Relevance
“…These findings indicated that the immobilized insulin did not enhance cell adhesion but transduced a signal to the cells through phos- phorylation of tyrosine residues of signal proteins. Previously, we reported that immobilized insulin activated insulin receptors, insulin receptor substrate-1 and phosphatidylinositol-3-kinase for a longer period than free insulin [12]. Therefore, even after 8 h of culture, activated cells were observed on the insulin immobilized region.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…These findings indicated that the immobilized insulin did not enhance cell adhesion but transduced a signal to the cells through phos- phorylation of tyrosine residues of signal proteins. Previously, we reported that immobilized insulin activated insulin receptors, insulin receptor substrate-1 and phosphatidylinositol-3-kinase for a longer period than free insulin [12]. Therefore, even after 8 h of culture, activated cells were observed on the insulin immobilized region.…”
Section: Resultsmentioning
confidence: 89%
“…The immobilized insulin activated the insulin receptor and downstream signaling proteins, and this activation persisted for longer periods than that with soluble insulin, probably explaining the greater mitogenic effect of the immobilized insulin [12]. In this study, signal transduction from the immobilized insulin was clearly visualized and the possibility of regulating cell functions through 'artificial juxtacrine stimulation' was examined using a micro-pattern-immobilized insulin.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[17] It was more than 20 years later when it was shown that low doses of insulin immobilized on polymers had higher mitogenic effect than free insulin. [18] Simultaneously, it was shown that epidermal GF (EGF) could be tethered to surfaces retaining its biological activity and with control of temporal and spatial availability. [19] However, besides these early successes it took another decade to investigate systematically the effect of GFs bound to surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized cytokines on the surface of a high molecular weight substrate continued to function without exhaustion of the cytokines. [14][15][16] Epidermal growth factor (EGF) among the various cytokines showed a ''juxtacrine stimulation'' effect to the target cells. 17,18 The present in vitro study was designed to examine the potential for early treatment of ACL injuries using an artificial juxtacrine cell culture model by a photo-immobilized EGF.…”
Section: Introductionmentioning
confidence: 99%